Persepsi Penghulu tentang Syarat Adil Saksi dan Implementasinya dalam Akad Nikah di KUA Kota Bukittinggi - Waridatul Hasanah; Adlan Sanur Tarihoran (Lembaga Yasin AlSys, 2026)
The status of witnesses in a marriage contract plays an important role in Islamic law, but the application of the requirement of moral probity for witnesses in service practices at the Offices of Religious Affairs (KUA) continues to face challenges, particularly in determining its indicators and assessment mechanisms. This study aims to analyze the perceptions of Islamic marriage registrars (penghulu) regarding the requirement of moral probity for witnesses and its implementation in the solemnization of marriage contracts at KUA offices throughout Bukittinggi City. The study employed a qualitative approach with a field research design. Data were collected through observation, interviews with Islamic marriage registrars, documentation, and a literature review and were subsequently analyzed through the stages of data collection, cleaning, organization, presentation, interpretation, and verification. The findings indicate that Islamic marriage registrars no longer interpret the concept of moral probity normatively and strictly as formulated in classical Islamic jurisprudence but assess it based on outward conditions, social reputation, and the principle of husnuzan. The implementation of the requirement of moral probity for witnesses tends to be administrative and social in nature, without an in-depth verification of the witnesses’ morality. The assessment focuses more on fulfilling formal requirements, including being Muslim, having reached puberty, being of sound mind, possessing clear identification, and being able to participate in the marriage contract process. These findings indicate a transformation in the interpretation of witness probity from a normative-theological concept toward a practical, administrative, and contextual approach. This study emphasizes the need for more detailed guidelines or standard operating procedures to standardize assessments of witness eligibility without disregarding service accessibility and the objectives of Islamic law.